Who Benefits from Globalization of Labor? Evidence from the 'Bosman Ruling' - Dafeng Xu (European Regional Science Association (ERSA), 2014)
As an old Chinese proverb says, "visiting monks give better sermons." European soccer clubs also believe this, and have always been seeking for foreign players to boost competitiveness. However, due to the reason of protectionism, there were restrictions that each club was only allowed to field up to three foreign players. In 1995, the "Bosman Ruling" was made, resulting that restrictions on foreign players were widely relaxed for soccer clubs in the European Union (EU), and the European soccer market has become highly globalized since then. Due to the nature of soccer competitions, it is impossible that the "Bosman Ruling" improves sporting performance for all clubs. It thus raises a question: who benefits from globalization of labor? From the perspective of economic inequality, will this ruling affect competitive balance of soccer leagues in Europe? This paper examines the pre- and post-Bosman change of the sporting performance distance between previously strong clubs and lower-ranking clubs in 32 premier soccer leagues in Europe. We notice the problem in the previous literature that estimations of the treatment effect of the "Bosman Ruling" are confounded with other soccer policy and rule changes. To solve this problem, we employ Difference-in-Difference-in-Differences (DDD) to control for omitted variables. Because the "Bosman Ruling" was made within the EU, it naturally created a Bosman region and a non-Bosman region. Using DDD, the treatment effect of the "Bosman Ruling" is identified at the distance-region-period level. Based on two sporting performance measures, i.e., the points per match and the goal difference per match, we estimate that the distance between previously strong and lower-ranking clubs increased by at least 20% in the post-Bosman period. Somewhat surprisingly, it is the distance between previously strong and median-ranking clubs that increased most, though the general pattern is that all lower-ranking clubs suffered loss. We also conduct IV regressions of the pre- and post-Bosman change of the distance between previously strong and lower-ranking clubs on the pre- and post-Bosman change of the number of foreign players in previously strong clubs. OLS can raise the endogeneity problem because sporting performance might also affect transfer decisions of foreign players. Therefore, we use the treatment variable (i.e., the dummy describing whether the club is in the Bosman region) as the instrument of the regressor, i.e., pre- and post-Bosman change of the number of foreign players. Similar with DDD estimations, we find that the influx of foreign players caused that the distance between previously strong and lower-ranking clubs increased after the "Bosman Ruling". Using both DDD and IV, we observe that previously strong clubs significantly benefited from globalization of labor. Soccer leagues in Europe became more unbalanced after the "Bosman Ruling".
Keywords: F66; L83; P25; R23; 330